Steel
By incorporating specific elements like Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, and Lu into steel, the hardenability is enhanced, achieving high martensite area ratios and improved strength-toughness balance at reduced costs.
Patent Information
- Application Number
- JP2023531405
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-28
- Filing Date
- 2022-03-11
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2042-03-11
AI Technical Summary
Existing steel materials face challenges in achieving high hardenability without relying on expensive elements like molybdenum, and there is a need for alternative alloying elements that can improve hardenability even in small amounts.
Incorporation of specific elements such as Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, and Sc into steel materials, along with precise control of their content and interaction with impurities like oxygen, nitrogen, and sulfur to enhance hardenability, as defined by specific chemical formulas and conditions.
The steel materials exhibit improved hardenability, maintaining a high martensite area ratio even at slow cooling rates, resulting in enhanced strength and toughness while reducing manufacturing costs.
Smart Images

Figure 0007617477000001 
Figure 0007617477000002 
Figure 0007617477000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel material. [Background technology]
[0002] It is generally known that in order to improve the material properties required for steel materials, particularly strength, it is effective to transform the metal structure into martensite and / or bainite by quenching. In relation to this, conventionally, alloy elements that improve hardenability have been added to steel materials to promote the transformation from austenite to martensite and / or bainite (see, for example, Patent Documents 1 to 5).
[0003] In the inventions described in Patent Documents 1 to 5, the critical cooling rate V at which the volume fraction of martensite becomes 90% or more is c is used as an index of hardenability. c The smaller the value, the higher the hardenability of the steel, and the martensite structure can be maintained even if the cooling rate is slow. Examples of alloying elements that improve hardenability include C, Si, Mn, Ni, Cr, Mo, and B. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-70970 A [Patent Document 2] International Publication No. 2013-175821 [Patent Document 3] International Publication No. 2012-144248 [Patent Document 4] JP 2007-291468 A [Patent Document 5] JP 2007-56283 A Summary of the Invention [Problem to be solved by the invention]
[0005] Molybdenum (Mo) is an element that is relatively effective in improving the hardenability of steel, but it is also an expensive element. Therefore, there is a need for steel materials that contain elements such as boron (B) that can improve hardenability even in small amounts.
[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a steel material having improved hardenability through a novel structure. [Means for solving the problem]
[0007] In order to achieve the above object, the present inventors have investigated elements capable of improving the hardenability of steel, and as a result, have found that specific elements significantly improve the hardenability of steel, thereby completing the present invention.
[0008] The steel materials that have achieved the above objectives are as follows: (1) In mass percent, C: 0.001 to 1.000%, Si: 0.01 to 3.00%, Mn: 0.10-4.50%, P: 0.300% or less, S: 0.0300% or less, Al: 0.001 to 5.000%, N: 0.2000% or less, O: 0.0100% or less, at least one X element selected from the group consisting of Pr: 0-0.8000%, Sm: 0-0.8000%, Eu: 0-0.8000%, Gd: 0-0.8000%, Tb: 0-0.8000%, Dy: 0-0.8000%, Ho: 0-0.8000%, Er: 0-0.8000%, Tm: 0-0.8000%, Yb: 0-0.8000%, Lu: 0-0.8000%, and Sc: 0-0.8000%, Nb: 0-3.000%, Ti: 0 to 0.500%, Ta: 0 to 0.500%, V: 0~1.00%, Cu: 0-3.00%, Ni: 0-16.00%, Cr: 0-15.00%, Mo: 0-5.00%, W: 0 to 2.00%, B: 0~0.0200%, Co: 0-3.00%, Be: 0~0.050%, Ag: 0~0.500%, Zr: 0 to 0.5000%, Hf: 0~0.5000%, Ca: 0 to 0.0500%, Mg: 0 to 0.0500%, At least one of La, Ce, Nd, Pm, and Y: 0 to 0.5000% in total; Sn: 0 to 0.300%, Sb: 0 to 0.300%, Te: 0~0.100%, Se: 0~0.100%, As: 0~0.050%, Bi: 0 to 0.500%, Pb: 0 to 0.500%, and The balance is composed of Fe and impurities. [X] calculated by the following formula 1 eff has a chemical composition that satisfies the following formula 2, Hardenability index V c and thickness t [mm] satisfy the following formula 3. [X] eff =0.40[Pr]+0.37[Sm]+0.37[Eu]+0.36[Gd]+0.35[Tb]+0.34[Dy]+0.34[Ho]+0. 33[Er]+0.33[Tm]+0.32[Yb]+0.32[Lu]+1.24[Sc]-2.33[O]-3.99[N]-1.74[S] ...Formula 1 [X] eff ≧0.0003...Equation 2 V c / (9773×t -1.8 )<1.00...Equation 3 However, when [B]<0.0003%, logVc =logV c1 =3.6-0.7×(2.7[C]+0.4[Si]+[Mn]+0.45[Ni]+0.8[Cr]+[Mo]+28[X] eff )...Equation 4 [B] ≧ 0.0003%, logV c =logV c2 =2.8-0.7×(2.7[C]+0.4[Si]+[Mn]+0.45[Ni]+0.8[Cr]+2[Mo]+37.9[X] eff )...Equation 5 Here, V c1 is the hardenability index V when the B content is less than 0.0003% c represents V c2 is the hardenability index V when the B content is 0.0003% or more. c and [Pr], [Sm], [Eu], [Gd], [Tb], [Dy], [Ho], [Er], [Tm], [Yb], [Lu], [Sc], [O], [N], [S], [B], [C], [Si], [Mn], [Ni], [Cr], and [Mo] are the contents of each element [mass %], and are 0 when the element is not contained. (2) When t≦16 mm, the hardenability index V c and the thickness t [mm] further satisfy the following formula 6. V c / 455exp(-0.36t)<1.00...Equation 6 (3) The steel material according to (1) or (2) above, in which the cleanliness of A-type inclusions as defined in JIS G 0555:2020 is 0.010% or less at a position of 1 / 4 of the thickness of the steel material. (4) The steel material according to any one of the above (1) to (3), having an N content of 0.0010% or more and an O content of 0.0010% or more. (5) The chemical composition is in mass%: Nb: 0.003 to 3.000%, Ti: 0.005 to 0.500%, Ta: 0.001 to 0.500%, V: 0.001 to 1.00%, Cu: 0.001-3.00%, Ni: 0.001 to 16.00%, Cr: 0.001~15.00%, Mo: 0.001 to 5.00%, W: 0.001 to 2.00%, B: 0.0001~0.0200%, Co: 0.001 to 3.00%, Be: 0.0003~0.050%, Ag: 0.001~0.500%, Zr: 0.0001 to 0.5000%, Hf: 0.0001~0.5000%, Ca: 0.0001 to 0.0500%, Mg: 0.0001 to 0.0500%, At least one of La, Ce, Nd, Pm, and Y: 0.0001 to 0.5000% in total; Sn: 0.001 to 0.300%, Sb: 0.001 to 0.300%, Te: 0.001~0.100%, Se: 0.001 to 0.100%, As: 0.001 to 0.050%, Bi: 0.001 to 0.500%, and Pb: 0.001~0.500% The steel material according to any one of (1) to (4) above, which contains one or more of the following: (6) The steel material according to any one of the above (1) to (4), wherein the Mg content is 0% or 0.0016 to 0.0500%. (7) The steel material according to any one of the above (1) to (6), having an Sn content of 0.004% or less. (8) The steel material according to any one of the above (1) to (7), wherein the martensite area ratio at a position halfway through the thickness of the steel material is 90% or more. (9) The steel material according to any one of the above (1) to (8), wherein the steel material has a thickness of 2.5 mm or more. Effect of the Invention
[0009] According to the present invention, a steel material having improved hardenability can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] <Steel> The steel material according to the embodiment of the present invention has, in mass%, C: 0.001 to 1.000%, Si: 0.01 to 3.00%, Mn: 0.10-4.50%, P: 0.300% or less, S: 0.0300% or less, Al: 0.001 to 5.000%, N: 0.2000% or less, O: 0.0100% or less, at least one X element selected from the group consisting of Pr: 0-0.8000%, Sm: 0-0.8000%, Eu: 0-0.8000%, Gd: 0-0.8000%, Tb: 0-0.8000%, Dy: 0-0.8000%, Ho: 0-0.8000%, Er: 0-0.8000%, Tm: 0-0.8000%, Yb: 0-0.8000%, Lu: 0-0.8000%, and Sc: 0-0.8000%, Nb: 0-3.000%, Ti: 0 to 0.500%, Ta: 0 to 0.500%, V: 0~1.00%, Cu: 0-3.00%, Ni: 0-16.00%, Cr: 0-15.00%, Mo: 0-5.00%, W: 0 to 2.00%, B: 0~0.0200%, Co: 0-3.00%, Be: 0~0.050%, Ag: 0~0.500%, Zr: 0 to 0.5000%, Hf: 0~0.5000%, Ca: 0 to 0.0500%, Mg: 0 to 0.0500%, At least one of La, Ce, Nd, Pm, and Y: 0 to 0.5000% in total; Sn: 0 to 0.300%, Sb: 0 to 0.300%, Te: 0~0.100%, Se: 0~0.100%, As: 0~0.050%, Bi: 0 to 0.500%, Pb: 0 to 0.500%, and The balance is composed of Fe and impurities. [X] calculated by the following formula 1 eff has a chemical composition that satisfies the following formula 2, Hardenability index V c and thickness t [mm] satisfy the following formula 3. [X] eff =0.40[Pr]+0.37[Sm]+0.37[Eu]+0.36[Gd]+0.35[Tb]+0.34[Dy]+0.34[Ho]+0. 33[Er]+0.33[Tm]+0.32[Yb]+0.32[Lu]+1.24[Sc]-2.33[O]-3.99[N]-1.74[S] ...Formula 1 [X] eff ≧0.0003 ···Equation 2 V c / (9773×t -1.8 )<1.00...Equation 3 However, when [B]<0.0003%, logV c =logV c1 =3.6-0.7×(2.7[C]+0.4[Si]+[Mn]+0.45[Ni]+0.8[Cr]+[Mo]+28[X] eff )...Equation 4 [B] ≧ 0.0003%, logV c =logV c2 =2.8-0.7×(2.7[C]+0.4[Si]+[Mn]+0.45[Ni]+0.8[Cr]+2[Mo]+37.9[X] eff )...Equation 5 Here, V c1is the hardenability index V when the B content is less than 0.0003% c represents V c2 is the hardenability index V when the B content is 0.0003% or more. c and [Pr], [Sm], [Eu], [Gd], [Tb], [Dy], [Ho], [Er], [Tm], [Yb], [Lu], [Sc], [O], [N], [S], [B], [C], [Si], [Mn], [Ni], [Cr], and [Mo] are the contents of each element [mass %], and are 0 when the element is not contained.
[0011] As described above, in order to transform the metal structure from austenite to martensite and / or bainite by quenching, it is necessary to include alloy elements that improve the hardenability in the steel material. However, for example, molybdenum (Mo), which acts relatively effectively to improve the hardenability of steel, is an expensive element. Therefore, it is preferable to use alloy elements such as boron (B) that can improve the hardenability even with a small amount of content.
[0012] From this viewpoint, the present inventors have investigated new elements capable of improving the hardenability of steel. As a result, the present inventors have found that by setting the amounts of specific elements dissolved in steel, namely, Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc elements (hereinafter also referred to as "X elements") within a predetermined range while taking into consideration the relationship with the inclusions formed by these elements in steel, more specifically, the oxides, nitrides, and sulfides of these elements (i.e., the effective amount [X] of the X element calculated by formula 1), eff The inventors have found that the hardenability of steel can be significantly improved even with a relatively small content of the X element by setting the effective amount of the X element [X] to 0.0003% or more and satisfying formula 2. eff and the content of other specific hardenable elements, c is appropriately determined in relation to the thickness t [mm] of the steel material (i.e., the hardenability index V determined by Equation 4 or Equation 5 depending on the B content). cand the thickness t [mm] of the steel material satisfy the formula 3. Therefore, according to the present invention, it is possible to relatively easily achieve a martensite area ratio of 90% or more at a position halfway through the thickness of the steel material even when the steel material is thick. Therefore, according to the present invention, it is possible to transform the metal structure into martensite, for example, to improve the strength, and also to reduce the manufacturing costs of the steel material.
[0013] Although it is not intended to be bound by any particular theory, it is believed that the above-mentioned X element according to the embodiment of the present invention segregates at the grain boundaries of austenite, and for example, suppresses ferrite transformation during cooling after hot rolling, and promotes transformation to martensite. To explain in more detail, in the cooling process after hot rolling, the metal structure transforms from austenite to ferrite or other structures, and it is known that, for example, the transformation from austenite to ferrite mainly occurs from the grain boundaries of austenite. In relation to this, it is believed that when the X element segregates at the grain boundaries of austenite, the energy of the grain boundaries can be relatively stabilized, and therefore it is possible to significantly reduce the frequency of ferrite formation from the grain boundaries. Therefore, it is believed that by including the X element in the steel material, it is possible to suppress ferrite transformation during the cooling process after hot rolling until the martensite transformation start temperature is reached, and as a result, it is possible to significantly promote the transformation from austenite to martensite.
[0014] However, there is a problem that the X element is likely to combine with O (oxygen), N (nitrogen) and S (sulfur) present in the steel to form inclusions consisting of oxides, nitrides and sulfides. If the X element forms such inclusions in the steel, the amount of the X element in solid solution that can contribute to improving the hardenability is reduced, and the hardenability improvement effect cannot be sufficiently obtained. In the present invention, the amount of the X element in solid solution taking such inclusions into consideration is calculated as the effective amount [X] of the X element by the above formula 1, which will be described in detail later. eff and the effective amount [X] effWithin the range of the above formula 2, that is, 0.0003% or more, it is possible to significantly improve the hardenability of the steel even with a relatively small content of the X element.
[0015] As described above, the X element in the present invention is likely to combine with O, N, and S to form inclusions, and therefore it is generally difficult to ensure a predetermined amount of solid solution in steel. For these reasons, the effect of improving hardenability due to the X element was not known in the past. However, with the recent progress in refining technology, it has become possible to reduce the contents of elements such as O, N, and S, which are generally present in steel as impurities, to a very low level, and this time, it has been possible to realize the solid solution of the X element within a predetermined range. Therefore, the effect of improving hardenability due to the solid solution of the X element has been revealed for the first time by the present inventors, which is extremely unexpected and surprising.
[0016] As described above, even a small amount of the X element has a sufficiently high effect of improving hardenability. However, in order to reliably achieve a high level of hardenability as a whole steel material, more specifically, a high martensite area ratio inside the steel material where hardening is more difficult, it is important to make the quantitative relationship between the X element and other specific hardenable elements appropriate in relation to the thickness of the steel material. In relation to this, the X element forms sulfides as inclusions as described above, which consumes S present in the steel, resulting in the suppression of the formation of MnS. Since Mn is an element that effectively acts to improve hardenability in addition to improving strength, the suppression of the formation of MnS due to the inclusion of the X element makes it possible to increase the amount of Mn that can contribute to improving hardenability. In the present invention, taking into consideration the influence between such hardenable elements, the effective amount [X] of the X element is set. eff and other specific hardenable element contents to determine the hardenability index V c is newly defined by the above formula 4 or formula 5, and the hardenability index V c is appropriate in relation to the thickness t [mm] of the steel material, that is, the hardenability index V cand the thickness t [mm] of the steel material satisfy the formula 3, it becomes possible to reliably achieve a martensite area ratio of 90% or more even inside the steel material where quenching is more difficult, for example, at a position halfway through the thickness of the steel material. Furthermore, according to the present invention, the metal structure can be made to be a uniform structure that is closer to a single phase mainly composed of martensite, so that a steel material that is hard but also improved in terms of toughness can be obtained.
[0017] Hereinafter, the steel material according to the embodiment of the present invention will be described in more detail. In the following description, the unit of content of each element, "%", means "mass%" unless otherwise specified. In addition, in this specification, "to" indicating a numerical range is used to mean that the numerical values before and after it are included as the lower limit and upper limit unless otherwise specified.
[0018] [C:0.001~1.000%] Carbon (C) is an element necessary for improving the hardenability of steel and stabilizing hardness and / or ensuring strength. To fully obtain these effects, the C content is 0.001% or more. The C content may be 0.005% or more, 0.010% or more, or 0.020% or more. On the other hand, if C is contained excessively, toughness, bendability, and / or weldability may decrease. Therefore, the C content is 1.000% or less. The C content may be 0.800% or less, 0.600% or less, or 0.500% or less.
[0019] [Si: 0.01-3.00%] Silicon (Si) is a deoxidizing element that improves the hardenability of steel and contributes to improving strength. To fully obtain these effects, the Si content is 0.01% or more. The Si content may be 0.05% or more, 0.10% or more, or 0.30% or more. On the other hand, excessive Si content may reduce toughness or cause surface quality defects called scale defects. Therefore, the Si content is 3.00% or less. The Si content may be 2.00% or less, 1.00% or less, or 0.60% or less.
[0020] [Mn: 0.10~4.50%] Manganese (Mn) is an element effective in improving hardenability and / or strength, and is also an effective austenite stabilizing element. To fully obtain these effects, the Mn content is 0.10% or more. The Mn content may be 0.50% or more, 0.70% or more, or 1.00% or more. On the other hand, excessive Mn content may generate MnS, which is harmful to toughness, or may reduce oxidation resistance. Therefore, the Mn content is 4.50% or less. The Mn content may be 4.00% or less, 3.50% or less, or 3.00% or less.
[0021] [P:0.300% or less] Phosphorus (P) is an element that is mixed in during the manufacturing process. The P content may be 0%. However, in order to reduce the P content to less than 0.0001%, refining takes time, which leads to a decrease in productivity. Therefore, the P content may be 0.0001% or more, 0.0005% or more, 0.001% or more, 0.003% or more, or 0.005% or more. From the viewpoint of manufacturing costs, the P content may be 0.007% or more. On the other hand, if P is contained excessively, the workability and / or toughness of the steel material may decrease. Therefore, the P content is 0.300% or less. The P content may be 0.100% or less, 0.030% or less, or 0.010% or less.
[0022] [S:0.0300% or less] Sulfur (S) is an element that is mixed in during the manufacturing process, and from the viewpoint of reducing inclusions formed with the X element according to the embodiment of the present invention, and further the generation of MnS that is harmful to toughness, the less the better, and therefore the S content may be 0%. However, reducing the S content to less than 0.0001% requires time for refining, which leads to a decrease in productivity. Therefore, the S content may be 0.0001% or more, 0.0005% or more, 0.0010% or more, 0.0015% or more, or 0.0020% or more. On the other hand, if S is contained excessively, the effective amount [X] of the X element is reduced. effThe S content is preferably 0.0100% or less, more preferably 0.0050% or less, and most preferably 0.0030% or less.
[0023] [Al: 0.001-5.000%] Aluminum (Al) is a deoxidizing element and is also an element effective in improving corrosion resistance and / or heat resistance. To obtain these effects, the Al content is 0.001% or more. The Al content may be 0.010% or more, 0.100% or more, or 0.200% or more. In particular, from the viewpoint of sufficiently improving heat resistance, the Al content may be 1.000% or more, 2.000% or more, or 3.000% or more. On the other hand, if Al is contained excessively, coarse inclusions may be generated to reduce toughness, problems such as cracks may occur during the manufacturing process, and / or fatigue resistance properties may be reduced. Therefore, the Al content is 5.000% or less. The Al content may be 4.500% or less, 4.000% or less, or 3.500% or less. In particular, from the viewpoint of suppressing a decrease in toughness, the Al content may be 1.500% or less, 1.000% or less, or 0.300% or less.
[0024] [N:0.2000% or less] Nitrogen (N) is an element that is mixed in during the manufacturing process, and from the viewpoint of reducing inclusions formed with the X element according to the embodiment of the present invention, the less the better, and therefore the N content may be 0%. However, in order to reduce the N content to less than 0.0001%, refining takes time, which leads to a decrease in productivity. Therefore, the N content may be 0.0001% or more, 0.0005% or more, 0.0010% or more, 0.0015% or more, 0.0020% or more, 0.0025% or more, or 0.0030% or more. On the other hand, N is also an element that is effective in stabilizing austenite, and may be intentionally contained as necessary. In this case, the N content is preferably 0.0100% or more, and may be 0.0200% or more, or 0.0500% or more. However, if N is contained excessively, the effective amount [X] of the X element may be reduced.eff The N content may decrease, and the toughness may decrease. Therefore, the N content is 0.2000% or less. The N content may be 0.1500% or less, 0.1000% or less, or 0.0800% or less.
[0025] [O:0.0100% or less] Oxygen (O) is an element that is mixed in during the manufacturing process, and from the viewpoint of reducing inclusions formed with the X element according to the embodiment of the present invention, the less the better, so the O content may be 0%. However, reducing the O content to less than 0.0001% requires time for refining, which leads to a decrease in productivity. Therefore, the O content may be 0.0001% or more, 0.0005% or more, 0.0010% or more, 0.0015% or more, 0.0020% or more, 0.0025% or more, or 0.0030% or more. On the other hand, if O is contained excessively, coarse inclusions are formed and the effective amount [X] of the X element is reduced. eff The O content may decrease, and the formability and / or toughness of the steel material may decrease. Therefore, the O content is 0.0100% or less. The O content may be 0.0080% or less, 0.0060% or less, or 0.0040% or less.
[0026] [At least one X element selected from the group consisting of Pr: 0-0.8000%, Sm: 0-0.8000%, Eu: 0-0.8000%, Gd: 0-0.8000%, Tb: 0-0.8000%, Dy: 0-0.8000%, Ho: 0-0.8000%, Er: 0-0.8000%, Tm: 0-0.8000%, Yb: 0-0.8000%, Lu: 0-0.8000%, and Sc: 0-0.8000%] The X elements according to the embodiment of the present invention are Pr: 0 to 0.8000%, Sm: 0 to 0.8000%, Eu: 0 to 0.8000%, Gd: 0 to 0.8000%, Tb: 0 to 0.8000%, Dy: 0 to 0.8000%, Ho: 0 to 0.8000%, Er: 0 to 0.8000%, Tm: 0 to 0.8000%, Yb: 0 to 0.8000%, Lu: 0 to 0.8000%, and Sc: 0 to 0.8000%. Praseodymium (Pr), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), and scandium (Sc) can exhibit a hardenability improvement effect by being present in austenite in a solid solution state. The hardenability improvement effect is thought to be exhibited by the X element segregating at the grain boundaries of austenite, for example, suppressing ferrite transformation during cooling after hot rolling and promoting transformation to martensite. By exhibiting the hardenability improvement effect, even with a relatively slow cooling rate, ferrite transformation can be suppressed until the martensite transformation start temperature is reached, and therefore transformation to martensite can be significantly promoted.
[0027] The X element may be used alone or in any specific combination of two or more of the above elements. The X element may be present in an amount that can ensure an effective amount, which will be described in detail later, and the lower limit is not particularly limited. However, for example, the content of each X element or the total content may be 0.0010% or more, preferably 0.0050% or more, more preferably 0.0150% or more, even more preferably 0.0300% or more, and most preferably 0.0500% or more. On the other hand, even if the X element is contained excessively, the effect is saturated, and therefore, the inclusion of the X element in the steel material more than necessary may lead to an increase in manufacturing costs. Therefore, the content of each X element may be 0.8000% or less, for example, 0.7000% or less, 0.6000% or less, 0.5000% or less, 0.4000% or less, or 0.3000% or less. The total content of the X elements is 9.6000% or less, and may be, for example, 6.0000% or less, 5.0000% or less, 4.0000% or less, 2.0000% or less, 1.0000% or less, or 0.5000% or less.
[0028] The basic chemical composition of the steel material according to the embodiment of the present invention is as described above. Furthermore, the steel material may contain one or more of the following optional elements as necessary. For example, the steel material may contain one or more of Nb: 0-3.000%, Ti: 0-0.500%, Ta: 0-0.500%, V: 0-1.00%, Cu: 0-3.00%, Ni: 0-16.00%, Cr: 0-15.00%, Mo: 0-5.00%, W: 0-2.00%, B: 0-0.0200%, Co: 0-3.00%, Be: 0-0.050%, and Ag: 0-0.500%. The steel material may contain one or more of Zr: 0-0.5000%, Hf: 0-0.5000%, Ca: 0-0.0500%, Mg: 0-0.0500%, and at least one of La, Ce, Nd, Pm, and Y: 0-0.5000% in total. The steel material may contain one or two of Sn: 0-0.300% and Sb: 0-0.300%. The steel material may contain one or two of Te: 0-0.100%, Se: 0-0.100%, As: 0-0.050%, Bi: 0-0.500%, and Pb: 0-0.500%. These optional elements will be described in detail below.
[0029] [Nb:0~3.000%] Niobium (Nb) is an element that contributes to precipitation strengthening and suppression of recrystallization. The Nb content may be 0%, but in order to obtain these effects, the Nb content is preferably 0.003% or more. For example, the Nb content may be 0.005% or more, 0.010% or more, 0.150% or more, or 0.200% or more. In particular, from the viewpoint of sufficiently achieving precipitation strengthening, the Nb content may be 1.000% or more or 1.500% or more. On the other hand, if Nb is excessively contained, the effect becomes saturated and the workability and / or toughness may be reduced. Therefore, the Nb content is 3.000% or less. The Nb content may be 2.800% or less, 2.500% or less, or 2.000% or less. In particular, from the viewpoint of suppressing a decrease in toughness of the weld heat affected zone (HAZ), the Nb content is preferably 0.100% or less, and may be 0.080% or less, 0.050% or less, or 0.030% or less. For example, the Nb content may be less than 0.005%, 0.004% or less, 0.003% or less, or 0.002% or less.
[0030] [Ti: 0~0.500%] Titanium (Ti) is an element that contributes to improving the strength of steel materials by precipitation strengthening and the like. The Ti content may be 0%, but in order to obtain such an effect, the Ti content is preferably 0.005% or more. The Ti content may be 0.010% or more, 0.050% or more, or 0.080% or more. On the other hand, if Ti is contained excessively, a large amount of precipitates may be generated, which may reduce toughness. Therefore, the Ti content is 0.500% or less. The Ti content may be 0.300% or less, 0.200% or less, or 0.100% or less.
[0031] [Ta: 0~0.500%] Tantalum (Ta) is an element effective for controlling the morphology of carbides and increasing strength. The Ta content may be 0%, but in order to obtain these effects, the Ta content is preferably 0.001% or more. The Ta content may be 0.005% or more, 0.010% or more, or 0.050% or more. On the other hand, if Ta is contained excessively, a large number of fine Ta carbides are precipitated, which leads to an excessive increase in the strength of the steel material, and as a result, there are cases in which the ductility and cold workability are reduced. Therefore, the Ta content is 0.500% or less. The Ta content may be 0.300% or less, 0.100% or less, or 0.080% or less.
[0032] [V:0~1.00%] Vanadium (V) is an element that contributes to improving the strength of steel materials by precipitation strengthening and the like. The V content may be 0%, but in order to obtain such an effect, the V content is preferably 0.001% or more. The V content may be 0.01% or more, 0.02% or more, 0.05% or more, or 0.10% or more. On the other hand, if V is contained excessively, a large amount of precipitates may be generated, which may reduce toughness. Therefore, the V content is 1.00% or less. The V content may be 0.80% or less, 0.60% or less, or 0.50% or less.
[0033] [Cu: 0-3.00%] Copper (Cu) is an element that contributes to improving strength and / or corrosion resistance. The Cu content may be 0%, but in order to obtain these effects, the Cu content is preferably 0.001% or more. The Cu content may be 0.01% or more, 0.10% or more, 0.15% or more, 0.20% or more, 0.30% or more, or 0.60% or more. On the other hand, excessive Cu content may cause deterioration of toughness and weldability. Therefore, the Cu content is 3.00% or less. The Cu content may be 2.00% or less, 1.50% or less, 1.00% or less, or 0.70% or less. For example, the Cu content may be less than 0.01%, 0.009% or less, 0.008% or less, or 0.006% or less.
[0034] [Ni:0~16.00%] Nickel (Ni) is an element that improves the hardenability of steel and contributes to improving strength and / or heat resistance, and is also an effective austenite stabilizing element. The Ni content may be 0%, but in order to obtain these effects, the Ni content is preferably 0.001% or more. The Ni content may be 0.01% or more, 0.10% or more, 0.50% or more, 0.70% or more, 1.00% or more, or 3.00% or more. On the other hand, excessive Ni content may increase the alloy cost as well as the deformation resistance during hot working, resulting in a large equipment load. Therefore, the Ni content is 16.00% or less. In particular, from the viewpoint of economy and / or suppressing the deterioration of weldability, the Ni content may be 15.00% or less, 10.00% or less, 6.00% or less, or 4.00% or less.
[0035] [Cr:0~15.00%] Chromium (Cr) is an element that enhances the hardenability of steel and contributes to improving strength and / or corrosion resistance. The Cr content may be 0%, but in order to obtain these effects, the Cr content is preferably 0.001% or more. The Cr content may be 0.01% or more, 0.05% or more, 0.10% or more, or 0.50% or more. On the other hand, excessive Cr content may increase the alloy cost and may reduce toughness. Therefore, the Cr content is 15.00% or less. In particular, from the viewpoint of suppressing the deterioration of weldability and / or workability, the Cr content may be 10.00% or less, 9.00% or less, 7.50% or less, 5.00% or less, or 2.50% or less.
[0036] [Mo:0~5.00%] Molybdenum (Mo) is an element that improves the hardenability of steel, contributes to improving strength, and also contributes to improving corrosion resistance. The Mo content may be 0%, but in order to obtain these effects, the Mo content is preferably 0.001% or more. The Mo content may be 0.01% or more, 0.02% or more, 0.50% or more, or 1.00% or more. On the other hand, if Mo is contained excessively, the deformation resistance during hot working increases, and the equipment load may become large. Therefore, the Mo content is 5.00% or less. The Mo content may be 4.50% or less, 4.00% or less, 3.00% or less, or 1.50% or less.
[0037] [W:0~2.00%] Tungsten (W) is an element that improves the hardenability of steel and contributes to improving strength. The W content may be 0%, but in order to obtain such an effect, the W content is preferably 0.001% or more. The W content may be 0.01% or more, 0.02% or more, 0.05% or more, 0.10% or more, or 0.50% or more. On the other hand, if W is contained excessively, ductility and weldability may decrease. Therefore, the W content is 2.00% or less. The W content may be 1.80% or less, 1.50% or less, or 1.00% or less.
[0038] [B:0~0.0200%] Boron (B) is an element that improves the hardenability of steel and contributes to improving strength. The B content may be 0%, but in order to obtain such an effect, the B content is preferably 0.0001% or more. The B content may be 0.0003% or more, 0.0005% or more, or 0.0007% or more. On the other hand, if B is contained excessively, toughness and / or weldability may decrease. Therefore, the B content is 0.0200% or less. The B content may be 0.0100% or less, 0.0050% or less, 0.0030% or less, or 0.0020% or less.
[0039] [Co: 0-3.00%] Cobalt (Co) is an element that contributes to improving hardenability and / or heat resistance. The Co content may be 0%, but in order to obtain these effects, the Co content is preferably 0.001% or more. The Co content may be 0.01% or more, 0.02% or more, 0.05% or more, 0.10% or more, or 0.50% or more. On the other hand, excessive Co content may deteriorate hot workability and lead to an increase in raw material costs. Therefore, the Co content is 3.00% or less. The Co content may be 2.50% or less, 2.00% or less, 1.50% or less, or 0.80% or less.
[0040] [Be:0~0.050%] Beryllium (Be) is an element effective in increasing the strength of the base material and refining the structure. The Be content may be 0%, but in order to obtain such an effect, the Be content is preferably 0.0003% or more. The Be content may be 0.0005% or more, 0.001% or more, or 0.010% or more. On the other hand, if Be is contained excessively, the formability may decrease. Therefore, the Be content is 0.050% or less. The Be content may be 0.040% or less, 0.030% or less, or 0.020% or less.
[0041] [Ag:0~0.500%] Silver (Ag) is an element effective in increasing the strength of the base material and refining the structure. The Ag content may be 0%, but in order to obtain such an effect, the Ag content is preferably 0.001% or more. The Ag content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.050% or more. On the other hand, if Ag is contained excessively, the formability may decrease. Therefore, the Ag content is 0.500% or less. The Ag content may be 0.400% or less, 0.300% or less, or 0.200% or less.
[0042] [Zr:0~0.5000%] Zirconium (Zr) is an element that can control the morphology of sulfides. The Zr content may be 0%, but in order to obtain such an effect, the Zr content is preferably 0.0001% or more. On the other hand, even if Zr is contained in excess, the effect saturates, and therefore, the inclusion of more Zr than necessary in steel may lead to an increase in manufacturing costs. Therefore, the Zr content is 0.5000% or less.
[0043] [Hf:0~0.5000%] Hafnium (Hf) is an element that can control the morphology of sulfides. The Hf content may be 0%, but in order to obtain such an effect, the Hf content is preferably 0.0001% or more. On the other hand, even if an excessive amount of Hf is contained, the effect is saturated, and therefore, the inclusion of more Hf than necessary in steel may lead to an increase in manufacturing costs. Therefore, the Hf content is 0.5000% or less.
[0044] [Ca: 0~0.0500%] Calcium (Ca) is an element that can control the morphology of sulfides. The Ca content may be 0%, but in order to obtain such an effect, the Ca content is preferably 0.0001% or more. On the other hand, even if an excessive amount of Ca is contained, the effect is saturated, and therefore, the inclusion of more Ca than necessary in the steel material may lead to an increase in manufacturing costs. Therefore, the Ca content is 0.0500% or less.
[0045] [Mg: 0~0.0500%] Magnesium (Mg) is an element capable of controlling the morphology of sulfides. The Mg content may be 0%, but in order to obtain such an effect, the Mg content is preferably 0.0001% or more. The Mg content may be more than 0.0015%, 0.0016% or more, 0.0017% or more, 0.0018% or more, 0.0019% or more, 0.0020% or more, 0.0022% or more, 0.0025% or more, 0.0028% or more, or 0.0030% or more. On the other hand, even if Mg is excessively contained, the effect is saturated, and the cold formability and / or toughness may decrease due to the formation of coarse inclusions. Therefore, the Mg content is 0.0500% or less. The Mg content may be 0.0400% or less, 0.0300% or less, or 0.0200% or less.
[0046] [At least one of La, Ce, Nd, Pm and Y: 0 to 0.5000% in total] Lanthanum (La), cerium (Ce), neodymium (Nd), promethium (Pm) and yttrium (Y) are elements that can control the morphology of sulfides, similar to Ca and Mg. The total content of at least one of La, Ce, Nd, Pm and Y may be 0%, but in order to obtain such an effect, it is preferable that it is 0.0001% or more. The total content of at least one of La, Ce, Nd, Pm and Y may be 0.0002% or more, 0.0003% or more, or 0.0004% or more. On the other hand, even if these elements are contained excessively, the effect may be saturated, and coarse oxides or the like may be formed, resulting in a decrease in cold formability. Therefore, the total content of at least one of La, Ce, Nd, Pm and Y may be 0.5000% or less, 0.4000% or less, 0.3000% or less, or 0.2000% or less.
[0047] [Sn: 0~0.300%] Tin (Sn) is an element effective in improving corrosion resistance. The Sn content may be 0%, but in order to obtain such an effect, the Sn content is preferably 0.001% or more. The Sn content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.050% or more. On the other hand, excessive Sn content may cause a decrease in toughness, particularly low-temperature toughness. Therefore, the Sn content is 0.300% or less. The Sn content may be 0.250% or less, 0.200% or less, or 0.150% or less. For example, the Sn content may be less than 0.005%, 0.004% or less, 0.003% or less, or 0.002% or less.
[0048] [Sb: 0~0.300%] Antimony (Sb) is an element effective for improving corrosion resistance like Sn, and the effect can be increased by including it in combination with Sn. The Sb content may be 0%, but in order to obtain the effect of improving corrosion resistance, the Sb content is preferably 0.001% or more. The Sb content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.050% or more. On the other hand, excessive Sb content may cause a decrease in toughness, particularly low-temperature toughness. Therefore, the Sb content is 0.300% or less. The Sb content may be 0.250% or less, 0.200% or less, or 0.150% or less.
[0049] [Te:0~0.100%] Tellurium (Te) is an element that is effective in improving the machinability of steel because it forms a low melting point compound with Mn, S, etc. to enhance the lubricating effect. The Te content may be 0%, but in order to obtain such an effect, the Te content is preferably 0.001% or more. The Te content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.040% or more. On the other hand, if Te is contained excessively, the effect becomes saturated and the alloy cost increases. Therefore, the Te content is 0.100% or less. The Te content may be 0.090% or less, 0.080% or less, or 0.070% or less.
[0050] [Se: 0~0.100%] Selenium (Se) is an effective element for improving the machinability of steel because selenides formed in steel change the shear plastic deformation of the workpiece and make chips more likely to be crushed. The Se content may be 0%, but in order to obtain such an effect, the Se content is preferably 0.001% or more. The Se content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.040% or more. On the other hand, if Se is contained excessively, the effect saturates and the alloy cost increases. Therefore, the Se content is 0.100% or less. The Se content may be 0.090% or less, 0.080% or less, or 0.070% or less.
[0051] [As: 0~0.050%] Arsenic (As) is an element effective in improving the machinability of steel. The As content may be 0%, but in order to obtain such an effect, the As content is preferably 0.001% or more. The As content may be 0.005% or more or 0.010% or more. On the other hand, if As is contained excessively, hot workability may be reduced. Therefore, the As content is 0.050% or less. The As content may be 0.040% or less, 0.030% or less, or 0.020% or less.
[0052] [Bi: 0~0.500%] Bismuth (Bi) is an element effective in improving the machinability of steel. The Bi content may be 0%, but in order to obtain such an effect, the Bi content is preferably 0.001% or more. The Bi content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.050% or more. On the other hand, if Bi is contained excessively, the effect saturates and the alloy cost increases. Therefore, the Bi content is 0.500% or less. The Bi content may be 0.400% or less, 0.300% or less, or 0.200% or less.
[0053] [Pb: 0~0.500%] Lead (Pb) is an element effective in improving the machinability of steel because it melts when the temperature rises during cutting and promotes the development of cracks. The Pb content may be 0%, but in order to obtain such an effect, the Pb content is preferably 0.001% or more. The Pb content may be 0.010% or more, 0.020% or more, 0.030% or more, or 0.050% or more. On the other hand, if Pb is contained excessively, hot workability may be reduced. Therefore, the Pb content is 0.500% or less. The Pb content may be 0.400% or less, 0.300% or less, or 0.200% or less.
[0054] In the steel material according to the embodiment of the present invention, the balance other than the above elements consists of Fe and impurities. The impurities are components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, when the steel material is industrially manufactured.
[0055] [Effective amount of element X [X] eff ] According to an embodiment of the present invention, an effective amount of X element [X] consisting of Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc is eff is calculated by the following formula 1, and its value is set to satisfy the following formula 2. [X] eff =0.40[Pr]+0.37[Sm]+0.37[Eu]+0.36[Gd]+0.35[Tb]+0.34[Dy]+0.34[Ho]+0. 33[Er]+0.33[Tm]+0.32[Yb]+0.32[Lu]+1.24[Sc]-2.33[O]-3.99[N]-1.74[S] ...Formula 1 [X] eff ≧0.0003 ···Equation 2 Here, [Pr], [Sm], [Eu], [Gd], [Tb], [Dy], [Ho], [Er], [Tm], [Yb], [Lu], [Sc], [O], [N], and [S] are the contents [mass%] of each element, and are 0 when the element is not contained.
[0056] Effective amount of X element calculated by the above formula [X]eff By making the above formula 2 satisfied (i.e., making it 0.0003 or more), the amount of these elements present in the steel in a solid solution state can be increased, and the hardenability can be improved. To explain in more detail, these X elements (hereinafter also simply referred to as "X") tend to combine with O (oxygen), N (nitrogen) and S (sulfur) present in the steel to form inclusions consisting of oxides (X2O3), nitrides (XN) and sulfides (XS). Once such inclusions are formed, at least the X elements in these inclusions cannot contribute to improving the hardenability. Therefore, in order to improve the hardenability, it is necessary to increase the amount of X elements present in the steel in a solid solution state without forming inclusions (i.e., the amount of X elements in the steel).
[0057] Here, the amount of the X element in solid solution in steel can be roughly calculated by subtracting the maximum amount that can be consumed to form inclusions (oxides, nitrides, and sulfides) from the amount of the X element contained in the steel. Therefore, in the embodiment of the present invention, the amount of the X element in solid solution roughly calculated in this manner is calculated as the amount of the X element effective for improving hardenability [X]. eff Specifically, it is defined by the following formula A. [X] eff [atomic%]=Σ(M [Fe] / M [X] )×[X]-(M [Fe] / M [O] )×[O]×2 / 3-(M [Fe] / M [N] )×[N]-(M [Fe] / M [S] )×[S]...Formula A Here, X represents each of the X elements Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc, and M [X] is the atomic weight of element X, M [Fe] is the atomic weight of Fe, M [O] is the atomic weight of O, M [N] is the atomic weight of N, M [S] represents the atomic weight of S, and [X], [O], [N] and [S] are the contents [mass %] of the corresponding elements, and are 0 when the element is not contained.
[0058] The above formula A will be explained in detail below. First, although the steel material according to the embodiment of the present invention contains various alloy elements, it is clear that the steel material as a whole is composed almost entirely of Fe, or, when the optional elements Ni and / or Cr are contained in a relatively large amount (the maximum contents are 16.00% and 15.00%, respectively), the steel material is composed almost entirely of Ni and / or Cr in addition to Fe. On the other hand, it is well known that the atomic weights of Ni and Cr are equivalent to the atomic weight of Fe. For this reason, even if the steel material contains a relatively large amount of Ni and / or Cr, the atomic % of each of the X elements Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc can be approximately calculated by multiplying the content [mass %] of each X element by the ratio of the atomic weight of Fe to the atomic weight of each X element, that is, (M [Fe] / M [X] ) × [X]. Therefore, (M [Fe] / M [X] ) × [X], i.e., Σ(M [Fe] / M [X] ) × [X], the atomic percentage of all X elements can be calculated.
[0059] Next, the amount of X element in steel that can effectively act to improve hardenability can be calculated by subtracting the maximum amount (atomic %) that can be consumed to form oxides (X2O3), nitrides (XN) and sulfides (XS) from the total atomic % of X element. Here, the maximum amount (atomic %) of X element that can be consumed to form oxides (X2O3), nitrides (XN) and sulfides (XS) can be calculated approximately by using the atomic weights of Fe, O, N and S in steel and the contents of O, N and S, respectively (M [Fe] / M [o] ) × [O] × 2 / 3, (M [Fe] / M [N] ) × [N], and (M [Fe] / M [S] ) × [S]. Therefore, the effective amount of X element for improving hardenability is [X] effcan be defined by the following formula A. [X] eff [atomic%]=Σ(M [Fe] / M [X] )×[X]-(M [Fe] / M [O] )×[O]×2 / 3-(M [Fe] / M [N] )×[N]-(M [Fe] / M [S] )×[S]...Formula A
[0060] Here, the atomic weights of Fe, O, N, S, and each X element are Fe: 55.845, O: 15.9994, N: 14.0069, S: 32.068, Pr: 140.908, Sm: 150.36, Eu: 151.964, Gd: 157.25, Tb: 158.925, Dy: 162.500, Ho: 164.930, Er: 167.259, Tm: 168.934, Yb: 173.045, Lu: 174.967, and Sc: 44.9559. Therefore, by substituting the atomic weights of each element into the above formula A and rearranging it, the effective amount [X] of the X element in atomic % is obtained. eff can be approximately expressed by the following formula 1. [X] eff =0.40[Pr]+0.37[Sm]+0.37[Eu]+0.36[Gd]+0.35[Tb]+0.34[Dy]+0.34[Ho]+0. 33[Er]+0.33[Tm]+0.32[Yb]+0.32[Lu]+1.24[Sc]-2.33[O]-3.99[N]-1.74[S] ...Formula 1 Here, [Pr], [Sm], [Eu], [Gd], [Tb], [Dy], [Ho], [Er], [Tm], [Yb], [Lu], [Sc], [O], [N], and [S] are the contents [mass%] of each element, and are 0 when the element is not contained.
[0061] In the embodiment of the present invention, in order to secure the amount of the X element in a solid solution state that contributes to improving the hardenability, the effective amount [X] of the X element calculated by the above formula 1 is eff It is necessary that the content of the SiC film is 0.0003% or more, that is, the following formula 2 is satisfied. [X]eff ≧0.0003 ···Equation 2 [X] eff may be, for example, 0.0005% or more or 0.0007% or more, preferably 0.0010% or more, more preferably 0.0015% or more, even more preferably 0.0030% or more, and most preferably 0.0050% or more or 0.0100% or more. [X] eff may be 0.0200% or more, 0.0300% or more, 0.0500% or more, 0.0800% or more, 0.1000% or more, 0.1200% or more, 0.1500% or more, 0.1800% or more, or 0.2000% or more. Also, as is clear from the above formula 1, [X] eff In order to stably secure the above, it is preferable to reduce the contents of O, N and S in the steel as much as possible. Here, [X] eff There is no particular upper limit for [X] eff Even if the content of [X] is excessively increased, the effect will saturate and the manufacturing cost will increase (the alloy cost will increase due to the increase in the content of the X element and / or the refining cost will increase due to O, N and S), which is not necessarily preferable. Therefore, [X] eff is preferably 2.0000% or less, and may be, for example, 1.8000% or less, 1.5000% or less, 1.2000% or less, 1.0000% or less, or 0.8000% or less.
[0062] [V c / (9773×t -1.8 )<1.00] In the embodiment of the present invention, in order to reliably achieve a high level of hardenability in the steel material as a whole, more specifically, a high martensite area ratio in the interior of the steel material, which is more difficult to harden, in addition to satisfying the above formula 2, the hardenability index V c and the thickness t [mm] of the steel material must satisfy the following formula 3. V c / (9773×t -1.8 )<1.00...Equation 3 However, when [B]<0.0003%, logV c =logV c1=3.6-0.7×(2.7[C]+0.4[Si]+[Mn]+0.45[Ni]+0.8[Cr]+[Mo]+28[X] eff )...Equation 4 [B] ≧ 0.0003%, logV c =logV c2 =2.8-0.7×(2.7[C]+0.4[Si]+[Mn]+0.45[Ni]+0.8[Cr]+2[Mo]+37.9[X] eff )...Equation 5 Here, V c1 is the hardenability index V when the B content is less than 0.0003% c represents V c2 is the hardenability index V when the B content is 0.0003% or more. c [B], [C], [Si], [Mn], [Ni], [Cr], and [Mo] are the contents of each element [mass %], and are 0 when the element is not contained.
[0063] Hardenability index V c [X] was determined by Jominy tests using steels with various chemical compositions. eff This formula was derived by examining the effect of other specific hardenable elements on the hardenability of steel. Specifically, the critical cooling rate V at which 90% or more of the metal structure becomes martensite is c90 In the formula, add the experimentally obtained [X] eff The term "hardenability index V" has been added. c When the B content is less than 0.0003%, V c1 It is determined by formula 4. When the B content is 0.0003% or more, V c2 and is determined by formula 5. Formula 4 is a formula when there is no effect of B on improving hardenability, and formula 5 is a formula when there is an effect of B on improving hardenability. Formula 3 is an empirical formula obtained by considering the relationship between the thickness of the steel material and the cooling rate at the 1 / 2 position of the thickness. With reference to formulas 4 and 5 above, [X] eff The coefficient of hardenability is 28 in formula 4 and 37.9 in formula 5, which is very large compared to the coefficients of other hardenability elements. cThe smaller the value, the better the hardenability. Therefore, from the above formulas 4 and 5, [X] eff It is clear that this steel has an extremely high effect of improving hardenability.
[0064] Therefore, according to the embodiment of the present invention, by satisfying the above-described formula 2, the transformation from austenite to martensite is promoted by the X element present in the steel in a solid solution state, and further, an effective amount of the X element [X] eff and the content of other specific hardenable elements, c By satisfying the formula 3 in relation to the thickness t [mm] of the steel material, it is relatively easy to achieve a martensite area ratio of 90% or more at a position halfway through the thickness of the steel material, even if the steel material is thick. c / (9773×t -1.8 The smaller the value of V, the better the hardenability, and therefore the value may be 0.95 or less, 0.90 or less, 0.85 or less, or 0.80 or less. c / (9773×t -1.8 The lower limit of V is not particularly limited and may be 0. For example, c / (9773×t -1.8 ) may be 0.01 or more, 0.05 or more, or 0.10 or more.
[0065] The thickness t of the steel material is not particularly limited and may be any appropriate thickness. For example, the thickness t of the steel material may be 0.1 mm or more, 0.6 mm or more, 1.2 mm or more, 1.5 mm or more, 1.8 mm or more, 2 mm or more, 2.2 mm or more, 2.5 mm or more, 2.8 mm or more, 3 mm or more, 3.5 mm or more, 4 mm or more, 5 mm or more, 6 mm or more, 8 mm or more, 10 mm or more, or more than 16 mm, and / or 250 mm or less, 200 mm or less, 150 mm or less, 120 mm or less, 100 mm or less, 90 mm or less, 80 mm or less, 50 mm or less, 30 mm or less, or 20 mm or less. The steel material may be a steel plate such as a thick steel plate or a thin steel plate, or may be a steel bar, a wire rod, a steel section, or a steel pipe. When the steel material is a steel plate, the thickness t means the plate thickness of the steel plate. When the steel material is a bar or wire rod, the thickness t means the diameter of the cross section perpendicular to the longitudinal direction of the bar or wire rod. When the steel material is a shaped steel, the thickness t means the thickness of the flange of the shaped steel. When the steel material is a steel pipe, the thickness t means the wall thickness of the steel pipe in the cross section perpendicular to the longitudinal direction.
[0066] [V c / 455exp(-0.36t)<1.00] The above formula 3 can be applied to any thickness t of the steel material. For example, when the thickness t of the steel material is 16 mm or less, the hardenability index V c and the thickness t [mm] of the steel material may further satisfy the following formula 6 in addition to the above formula 3. V c / 455exp(-0.36t)<1.00...Equation 6 Formula 6 is an empirical formula obtained by considering the relationship between the thickness of the steel material and the cooling rate at the 1 / 2 position of the thickness, particularly limiting the thickness of the steel material to 16 mm or less. c The smaller the value of / 455exp(-0.36t) is, the better the hardenability is. Therefore, the value may be 0.95 or less, 0.90 or less, 0.85 or less, or 0.80 or less. c The lower limit of / 455exp(-0.36t) is not particularly limited and may be 0. For example, V c / 455exp(-0.36t) may be 0.01 or greater, 0.05 or greater, or 0.10 or greater.
[0067] [A-type inclusion cleanliness: 0.010% or less] In an embodiment of the present invention, the cleanliness of the A-type inclusions as defined in JIS G 0555:2020 is preferably 0.010% or less at a position of 1 / 4 of the thickness of the steel material. In the present invention, the A-type inclusions refer to the A-type inclusions as defined in JIS G 0555:2020, which are soft inclusions such as MnS that are stretched in the rolling direction by hot rolling and become elongated. When A-type inclusions stretched in the rolling direction are present, material anisotropy occurs, and for example, such A-type inclusions may cause anisotropy in toughness or strengthen the anisotropy of toughness because they become the starting point of cracks in a specific direction. As described above, the X element forms sulfides as inclusions, and as a result, S present in the steel is consumed. The sulfides of the X element are relatively hard, and unlike A-type inclusions such as MnS, they are not stretched in the rolling direction or are not stretched significantly in the rolling direction. Therefore, by including a sufficient amount of the X element in the steel material, the cleanliness of the A-type inclusions can be improved, and as a result, the material anisotropy of the steel material, more specifically, the anisotropy of toughness, can be reduced. From the viewpoint of reducing the anisotropy of toughness, the lower the cleanliness of the A-type inclusions, the more preferable, and for example, it may be 0.009% or less, 0.008% or less, 0.007% or less, or 0.005% or less. The lower limit of the cleanliness of the A-type inclusions is not particularly limited and may be 0%. For example, the cleanliness of the A-type inclusions may be 0.001% or more, or 0.002% or more.
[0068] In the present invention, the cleanliness of the A-type inclusions is determined by the so-called "point counting method" in which observation is performed with an optical microscope at a measurement field number of 60 and a magnification of 400 times, as described in JIS G 0555:2020 "Microscopic test method for non-metallic inclusions in steel".
[0069] [Metal structure] According to the embodiment of the present invention, a martensite area ratio of 90% or more can be achieved at the 1 / 2 position of the steel material thickness. The 1 / 2 position of the steel material thickness is the portion where the cooling rate is the slowest, and therefore the portion where hardening is most difficult. However, the steel material according to the embodiment of the present invention has a chemical composition that satisfies the formula 2 and has a hardenability index V c By making the thickness t [mm] satisfy the formula 3, the X element having an extremely high effect of improving hardenability can be effectively used, and the ferrite transformation can be significantly suppressed until the martensite transformation start temperature is reached even at a relatively slow cooling rate. Therefore, according to the embodiment of the present invention, not only a relatively thin steel material but also a thick steel material that is more difficult to harden can be sufficiently hardened to the inside, and a high martensite area ratio can be achieved at the position of 1 / 2 the thickness of the steel material. The martensite area ratio at the position of 1 / 2 the thickness of the steel material is preferably 92% or more, more preferably 95% or more, even more preferably 98% or more, and most preferably 100%.
[0070] The area ratio of martensite is determined as follows. First, an L-section (a section parallel to the rolling direction and thickness direction of the steel) at a position half the thickness of the steel is mirror-polished, then etched with nital, and three observation fields of 500 μm×500 μm are randomly selected using an optical microscope, the area ratio of martensite is measured in each observation field, and the area ratio is determined by averaging them. Here, martensite is a lath-shaped structure observed by the above method, and is not limited to fresh martensite, but also includes tempered martensite and lower bainite.
[0071] [Mechanical properties] According to the embodiment of the present invention, as described above, the metal structure can be made uniform and closer to a single phase, mainly composed of martensite, so that excellent toughness can be achieved despite the hardness. More specifically, the toughness can be achieved such that the average value of the Charpy absorbed energy (KV2) at -20°C is 20J or more, preferably 30J or more, more preferably 40J or more, and most preferably 45J or more. The upper limit of the average value of the Charpy absorbed energy is not particularly limited, but may be, for example, 100J. The average value of the Charpy absorbed energy is calculated by measuring three Charpy absorbed energies at -20°C using an impact blade with a radius of 2 mm in accordance with the provisions of JIS Z 2242:2018 based on a V-notch test piece obtained by taking a sample from a position at 1 / 4 of the thickness of the steel material and putting a notch in the width direction (C direction) of the steel material. When a sub-size test piece is used, it is converted to a full-size Charpy absorbed energy according to the thickness of the test piece.
[0072] According to a preferred embodiment of the present invention, the cleanliness of the A-type inclusions is 0.010% or less, thereby improving the material isotropy. More specifically, the L / C ratio of the Charpy absorbed energy in the rolling direction (L direction) and the width direction (C direction) in the Charpy impact test is 0.6 to 1.2, and the anisotropy of the toughness can be significantly reduced. From the viewpoint of improving the material isotropy or reducing the anisotropy of the toughness, the L / C ratio is preferably closer to 1.0, and may be, for example, 0.7 or more, and / or 1.1 or less, or 1.0 or less. In a V-notch test piece notched in the L direction, a crack generated from the notch bottom propagates along the L direction, so that the Charpy absorbed energy decreases when affected by the A-type inclusions. When the L / C ratio exceeds 1.0, the Charpy absorbed energy in the L direction and the C direction are equivalent, and it may be considered that the measurement error is the cause.
[0073] The L / C ratio is determined as follows: First, a V-notch test piece is prepared by taking a sample from a position 1 / 4 of the thickness of the steel material and putting a notch in the rolling direction (L direction) or width direction (C direction) of the steel material, and then a Charpy impact test is performed at -20°C using an impact blade with a radius of 2 mm in accordance with the provisions of JIS Z 2242:2018, and the L / C ratio is determined by calculating the ratio between the Charpy absorbed energy of the V-notch test piece notched in the L direction (average of three measured values) and the Charpy absorbed energy of the V-notch test piece notched in the C direction (average of three measured values).
[0074] The steel material according to the embodiment of the present invention may be any steel material and is not particularly limited. The steel material according to the embodiment of the present invention includes, for example, thick steel plate, thin steel plate, and further, steel bar, wire rod, shaped steel, steel pipe, and the like. The thickness t of the steel material according to the embodiment of the present invention is, for example, 0.1 mm to 250 mm. When the steel material according to the embodiment of the present invention is a thick steel plate, the thickness t is, for example, 3 mm to 250 mm or 6 mm to 250 mm. When the steel material according to the embodiment of the present invention is a thin steel plate, the thickness t is, for example, 0.1 mm to 16 mm. In the case of a steel bar or wire rod, the diameter of the cross section perpendicular to the longitudinal direction is, for example, 1.0 mm to 250 mm. In the case of shaped steel, the thickness of the flange is, for example, 20 mm to 150 mm. In the case of a steel pipe, the thickness (wall thickness) of the cross section perpendicular to the longitudinal direction is, for example, 1.0 mm to 160 mm.
[0075] The steel material according to the embodiment of the present invention can be manufactured by any appropriate method known to those skilled in the art depending on the form of the final product, etc. For example, when the steel material is a thick steel plate, the manufacturing method includes the steps generally applied when manufacturing a thick steel plate, for example, the step of casting a slab having the above-described chemical composition, the step of hot rolling the cast slab, and the step of cooling the obtained rolled material, and may further include an appropriate heat treatment step, a tempering step, etc. as necessary.
[0076] In addition, when the steel material is a thin steel plate, the manufacturing method thereof includes steps generally applied when manufacturing a thin steel plate, for example, a step of casting a slab having the above-described chemical composition, a step of hot rolling the cast slab, and a step of cooling and coiling the obtained rolled material, and may further include a cold rolling step, an annealing step, etc. as necessary. Similarly, the manufacturing method of a steel bar or other steel material includes steps generally applied when manufacturing a steel bar or other steel material, for example, a steelmaking step of forming a molten steel having the above-described chemical composition, a step of casting a slab, billet, bloom, etc. from the formed molten steel, a step of hot rolling the cast slab, billet, bloom, etc., and a step of cooling the obtained rolled material, and other steps can be appropriately selected and performed from appropriate steps known to those skilled in the art for manufacturing those steel materials.
[0077] Since the steel material according to the embodiment of the present invention has significantly improved hardenability, it is possible to sufficiently harden the steel material to the inside even if the cooling rate after hot rolling or cooling after annealing is relatively slow. For example, in order to achieve a martensite area ratio of 90% or more at a position halfway through the thickness of the steel material, the cooling rate after hot rolling or cooling after annealing is set to a hardening index V c Taking into consideration the specific values of the thickness of the steel material and the like, an appropriate average cooling rate may be selected from the range of 0.3 to 200°C / sec, and cooling may be performed to a temperature below the martensitic transformation start temperature, for example, 400°C or less, 300°C or less, or 200°C or less. The specific conditions for each of the other steps are not particularly limited, and appropriate conditions may be appropriately selected depending on the type of steel, the type and shape of the steel material, etc. In the production of the steel material according to the embodiment of the present invention, an effective amount [X] of the X element that contributes to improving hardenability is added. eff It is important to ensure that the X element and the contents of O, N and S, which can form inclusions in the steel, are sufficiently reduced in the refining process.
[0078] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way. EXAMPLES
[0079] [Example A] In this example, first, slabs having various chemical compositions were cast, cut to obtain steel billets, and then hot rolling was performed at a rolling reduction rate of 50% or more, followed by cooling. Next, the obtained rolled material was heated to a predetermined temperature in the range of 950 to 1100 ° C., and then cooled to 400 ° C. or less at an average cooling rate appropriately selected from the range of 0.5 to 150 ° C. / sec according to the thickness t (mm) to obtain steel materials (when the thickness of the rolled material is thick, a higher average cooling rate is applied, and when the thickness is the same, the same average cooling rate is applied). The chemical compositions obtained by analyzing samples taken from each of the obtained steel materials are as shown in Table 1 below. The thickness of each of the obtained steel materials is also as shown in Table 1 below. The metal structure of the sample taken from the position of 1 / 2 of the thickness of each of the obtained steel materials was observed by an optical microscope, and the area ratio of martensite was measured. The L-section of the sample was mirror-polished and then etched with nital. Three observation fields of 500 μm × 500 μm were randomly selected using an optical microscope, and the area fraction of martensite (lath-like structure) in each observation field was measured. These were then averaged to determine the area fraction of martensite (M area fraction), which is shown in Table 1.
[0080] [Table 1-1]
[0081] [Table 1-2]
[0082] [Table 1-3]
[0083] [Table 1-4]
[0084] [Table 1-5]
[0085] [Table 1-6]
[0086] In this example, when the area ratio of martensite (M area ratio) is 90% or more, the steel material is evaluated as having improved hardenability. Referring to Table 1, in Comparative Examples 84 to 89, the effective amount [X] of X element is eff Since the amount of the X element is low and formula 3 is not satisfied, the hardenability is insufficient and the area ratio of martensite is less than 90%. eff was higher than 0.0003%, and therefore satisfied formula 2, but did not satisfy formula 3 in relation to other hardenable elements, resulting in insufficient hardenability and a martensite area fraction of less than 90%. In contrast, in all examples according to the present invention, a martensite area fraction of 90% or more could be achieved by satisfying formulas 2 and 3, and high hardenability could be exhibited.
[0087] [Example B] In this example, a steel slab taken from a part of the slab of Example A was used, and hot rolling was performed with a rolling reduction rate larger than that of Example A, and then cooled. The obtained rolled material was heated to a predetermined temperature in the range of 950 to 1100 ° C., and then cooled to 400 ° C. or less at an average cooling rate appropriately selected from the range of 0.7 to 60 ° C. / sec according to the thickness t (mm) to obtain a steel material (when the thickness of the rolled material is thick, a higher average cooling rate is applied, and when the thickness is the same, the same average cooling rate is applied). The thickness of each steel material obtained is as shown in Table 2 below. The area ratio of martensite (M area ratio) of each steel material obtained was measured in the same manner as in Example A. A sample was taken from a position of 1 / 4 of the thickness of the steel material, and an optical microscope observation was performed at the L cross section with a measurement field number of 60 and a magnification of 400 times, and the cleanliness of A-type inclusions specified in JIS G 0555:2020 was determined by the "point calculation method". A full-size V-notch test piece was taken from 1 / 4 of the thickness of the steel material and notched in the L or C direction of the steel material, and a Charpy impact test was performed at -20°C using an impact blade with a radius of 2 mm in accordance with the provisions of JIS Z 2242:2018. The Charpy absorbed energy in the C direction was measured for three pieces and averaged to obtain the average Charpy absorbed energy (KV2). Similarly, the Charpy absorbed energy in the L and C directions was calculated by averaging the measured values of three test pieces each, and the L / C ratio was calculated. The results are shown in Table 2.
[0088] [Table 2-1]
[0089] [Table 2-2]
[0090] In this example, similarly to Example A, when the area ratio of martensite (M area ratio) was 90% or more, the steel was evaluated as having improved hardenability. Referring to Table 2, in Comparative Examples 135 and 136, the effective amount [X] of X element was effSince the amount of the X element is low and formula 3 is not satisfied, the hardenability is insufficient and it is not possible to obtain a uniform structure close to a single phase with an area ratio of martensite of 90% or more, and as a result, the average value of the Charpy absorbed energy (KV2) is low in Comparative Example 135. Also, in Comparative Examples 135 and 136, it is considered that the S in the steel was not sufficiently consumed because the content of the X element was relatively small, and as a result, A-based inclusions such as MnS increased, the cleanliness exceeded 0.010%, and the L / C ratio was low. On the other hand, in Comparative Example 137, the effective amount [X] of the X element was too low, and the average value of the Charpy absorbed energy (KV2) was too low. eff was higher than 0.0003%, and therefore satisfied formula 2, but did not satisfy formula 3 in relation to other hardenable elements, resulting in insufficient hardenability, and similarly, a uniform structure close to a single phase with a martensite area ratio of 90% or more could not be obtained, resulting in a decrease in the average Charpy absorbed energy (KV2). In contrast, in all examples according to the present invention, a martensite area ratio of 90% or more could be achieved by satisfying formulas 2 and 3, and high hardenability could be exhibited. In addition, in all examples according to the present invention, the average Charpy absorbed energy (KV2) at -20°C was 20J or more, and excellent toughness was achieved, while the L / C ratio was within the range of 0.6 to 1.2, thereby reducing the anisotropy of toughness.
[0091] [Example C: Steel material with a thickness of 16 mm or less] In this example, a steel material having a thickness of 16 mm or less was manufactured, and its characteristics were examined. Specifically, a steel slab taken from a part of the slab of Example A was used, and hot rolling was performed with a rolling reduction rate larger than that of Example A, and then cooled. The obtained rolled material was heated to a predetermined temperature in the range of 950 to 1100°C, and then cooled to 400°C or less at an average cooling rate appropriately selected from the range of 2.0 to 160°C / sec depending on the thickness t (mm) to obtain a steel material (a higher average cooling rate is applied when the thickness of the rolled material is thick, and the same average cooling rate is applied when the thickness is the same). The thickness of each steel material obtained is as shown in Table 3 below. The area ratio of martensite (M area ratio) and the cleanliness of A-type inclusions of each obtained steel material were measured in the same manner as in Example B. Sub-size (2.5 mm) V-notch test pieces were taken from 1 / 4 of the thickness of the steel material and notched in the L or C direction of the steel material, and the average Charpy absorbed energy (KV2) and L / C ratio were calculated in the same manner as in Example B. The average Charpy absorbed energy was converted to a full-size value. The results are shown in Table 3.
[0092] [Table 3-1]
[0093] [Table 3-2]
[0094] In this example, similarly to Examples A and B, when the area ratio of martensite (M area ratio) was 90% or more, the steel was evaluated as having improved hardenability. Referring to Table 3, in Comparative Example 227, the effective amount [X] of X element was eff Since the amount of the X element was low and formulas 3 and 6 were not satisfied, the hardenability was insufficient and it was not possible to achieve a martensite area ratio of 90% or more. In Comparative Example 227, it is considered that the S in the steel was not sufficiently consumed because the content of the X element was relatively small, and as a result, the A-type inclusions such as MnS increased, the cleanliness exceeded 0.010%, and the L / C value decreased. On the other hand, in Comparative Example 228, the effective amount [X] of the X element was low, and the S in the steel was not sufficiently consumed because the content of the X element was relatively low. As a result, the A-type inclusions such as MnS increased, the cleanliness exceeded 0.010%, and the L / C value decreased. effwas higher than 0.0003%, and therefore satisfied formula 2, but did not satisfy formulas 3 and 6 in relation to other hardenable elements, resulting in insufficient hardenability, and similarly, a uniform structure close to a single phase with an area ratio of martensite of 90% or more could not be obtained, resulting in a decrease in the average value of Charpy absorbed energy (KV2). In contrast, in all examples according to the present invention, a martensite area ratio of 90% or more could be achieved by satisfying formulas 2 and 3, and further formula 6, and high hardenability could be exhibited. In addition, in all examples according to the present invention, the average value of Charpy absorbed energy (KV2) at -20°C was 20J or more, and excellent toughness was achieved, while the L / C ratio was within the range of 0.6 to 1.2, thereby reducing the anisotropy of toughness. [Industrial Applicability]
[0095] The steel material according to the embodiment of the present invention is, for example, a steel material after hot rolling. The steel material after hot rolling includes, for example, thick steel plates used for applications such as bridges, architecture, shipbuilding, and pressure vessels, thin steel plates used for applications such as automobiles and home appliances, and also steel bars, wire rods, shaped steel, and steel pipes. When the steel material according to the embodiment of the present invention is applied to these materials, a high-strength steel material can be manufactured due to the effect of improving hardenability. In addition, since the metal structure can be made a uniform structure closer to a single phase than that mainly composed of martensite, it is possible to significantly improve, for example, toughness despite the high strength.
Claims
1. In mass percent, C: 0.001-1.000%, Si: 0.01-3.00%, Mn: 0.10 to 4.50%, P: 0.300% or less, S: 0.0300% or less, Al: 0.001-5.000%, N: 0.2000% or less, O: 0.0100% or less, at least one X element selected from the group consisting of Pr: 0 to 0.8000%, Eu: 0 to 0.8000%, Gd: 0 to 0.8000%, Tb: 0 to 0.8000%, Dy: 0 to 0.8000%, Ho: 0 to 0.8000%, Er: 0 to 0.8000%, Tm: 0 to 0.8000%, Yb: 0 to 0.8000%, Lu: 0 to 0.8000%, and Sc: 0 to 0.8000%, Nb: 0 to 3.000%, Ti: 0 to 0.500%, Ta: 0-0.500%, V: 0-1.00%, Cu: 0-3.00%, Ni: 0 to 16.00%, Cr: 0-15.00%, Mo: 0-5.00%, W: 0-2.00%, B: 0 to 0.0200%, Co: 0-3.00%, Be: 0 to 0.050%, Ag: 0-0.500%, Zr: 0 to 0.5000%, Hf: 0-0.5000%, Ca: 0-0.0500%, Mg: 0% or 0.0016 to 0.0500%, At least one of La, Ce, Nd, Pm, and Y: 0 to 0.5000% in total, Sn: 0-0.300%, Sb: 0 to 0.300%, Te: 0 to 0.100%, Se: 0 to 0.100%, As: 0 to 0.050%, Bi: 0-0.500%, Pb: 0 to 0.500%, and The balance is composed of Fe and impurities. [X] calculated by the following formula 1 eff has a chemical composition that satisfies the following formula 2: Hardenability index V c and thickness t [mm] satisfy the following formula 3. [X] eff =0.40 [Pr] +0.37 [Eu] +0.36 [Gd] +0.35 [Tb] +0.34 [Dy] +0.34 [Ho] +0.33 [Er] +0.33 [Tm] +0.32 [Yb] +0.32 [Lu] +1.24 [Sc] - 2.33 [O] - 3.99 [N] - 1.74 [S] ..... Equation 1 [X] eff ≧0.0003 ……Formula 2 V c / (9773×t -1.8 )<1.00 ……Formula 3 However, when [B] is less than 0.0003%, logV c = logV c1 = 3.6 - 0.7×(2.7[C] + 0.4[Si] + [Mn] + 0.45[Ni] + 0.8[Cr] + [Mo] + 28[X] eff )... Equation 4 [B] ≧0.0003%, logV c = logV c2 = 2.8 - 0.7×(2.7[C] + 0.4[Si] + [Mn] + 0.45[Ni] + 0.8[Cr] + 2[Mo] + 37.9[X] eff )... Equation 5 Here, V c1 is the hardenability index V when the B content is less than 0.0003% c represents V c2 is the hardenability index V when the B content is 0.0003% or more c and [Pr], [Eu], [Gd], [Tb], [Dy], [Ho], [Er], [Tm], [Yb], [Lu], [Sc], [O], [N], [S], [B], [C], [Si], [Mn], [Ni], [Cr], and [Mo] are the contents [mass %] of each element, and are 0 when the element is not contained.
2. In mass %, C: 0.001-1.000%, Si: 0.01-3.00%, Mn: 0.10 to 4.50%, P: 0.300% or less, S: 0.0300% or less, Al: 0.001-5.000%, N: 0.2000% or less, O: 0.0100% or less, at least one X element selected from the group consisting of Pr: 0 to 0.8000%, Sm: 0 to 0.8000%, Eu: 0 to 0.8000%, Gd: 0 to 0.8000%, Tb: 0 to 0.8000%, Dy: 0 to 0.8000%, Ho: 0 to 0.8000%, Er: 0 to 0.8000%, Tm: 0 to 0.8000%, Yb: 0 to 0.8000%, Lu: 0 to 0.8000%, and Sc: 0 to 0.8000%, Nb: 0-3.000%, Ti: 0 to 0.500%, Ta: 0-0.500%, V: 0-1.00%, Cu: 0-3.00%, Ni: 0 to 16.00%, Cr: 0-15.00%, Mo: 0-5.00%, W: 0-2.00%, B: 0 to 0.0200%, Co: 0-3.00%, Be: 0 to 0.050%, Ag: 0-0.500%, Zr: 0 to 0.5000%, Hf: 0-0.5000%, Ca: 0-0.0500%, Mg: 0% or 0.0016 to 0.0500%, At least one of La, Ce, Nd, Pm, and Y: 0 to 0.5000% in total, Sn: 0-0.300%, Sb: 0 to 0.300%, Te: 0 to 0.100%, Se: 0-0.100%, As: 0 to 0.050%, Bi: 0-0.500%, Pb: 0 to 0.500%, and The balance is composed of Fe and impurities. The [X]eff calculated by the following formula 1 has a chemical composition that satisfies the following formula 2, The hardenability index Vc and the thickness t [mm] satisfy the following formula 3: When t≦16 mm, the hardenability index V c and the thickness t [mm] further satisfies the following formula 6. [X]eff =0.40[Pr]+0.37[Sm]+0.37[Eu]+0.36[Gd]+0.35[Tb]+0.34[Dy]+0.34[Ho]+0. 33[Er]+0.33[Tm]+0.32[Yb]+0.32[Lu]+1.24[Sc]-2.33[O]-3.99[N]-1.74[S] ...Formula 1 [X] eff ≧0.0003 ... Formula 2 V c / (9773×t -1.8 )<1.00...Formula 3 V c / 455exp(-0.36t)<1.00 ……Formula 6 However, when [B] is less than 0.0003%, logV c =logV c1 =3.6-0.7×(2.7[C]+0.4[Si]+[Mn]+0.45[Ni]+0.8[Cr]+[Mo]+28[X]eff) ...Formula 4 [B] ≧0.0003%, logV c =logV c2 =2.8-0.7×(2.7[C]+0.4[Si]+[Mn]+0.45[Ni]+0.8[Cr]+2[Mo]+37.9[X]eff) ...Formula 5 Here, Vc1 represents the hardenability index Vc when the B content is less than 0.0003%, Vc2 represents the hardenability index Vc when the B content is 0.0003% or more, and [Pr], [Sm], [Eu], [Gd], [Tb], [Dy], [Ho], [Er], [Tm], [Yb], [Lu], [Sc], [O], [N], [S], [B], [C], [Si], [Mn], [Ni], [Cr], and [Mo] are the contents [mass %] of each element, and are 0 when the element is not contained.
3. The steel material according to claim 1 or 2, wherein the cleanliness of A-type inclusions as defined in JIS G 0555:2020 is 0.010% or less at a position of 1 / 4 of the thickness of the steel material.
4. The steel material according to any one of claims 1 to 3, wherein the N content is 0.0010% or more and the O content is 0.0010% or more.
5. The chemical composition, in mass%, Nb: 0.003 to 3.000%, Ti: 0.005-0.500%, Ta: 0.001 to 0.500%, V: 0.001-1.00%, Cu: 0.001 to 3.00%, Ni: 0.001 to 16.00%, Cr: 0.001-15.00%, Mo: 0.001 to 5.00%, W: 0.001-2.00%, B: 0.0001 to 0.0200%, Co: 0.001-3.00%, Be: 0.0003-0.050%, Ag: 0.001-0.500%, Zr: 0.0001 to 0.5000%, Hf: 0.0001-0.5000%, Ca: 0.0001-0.0500%, Mg: 0.0016-0.0500%, At least one of La, Ce, Nd, Pm, and Y: 0.0001 to 0.5000% in total, Sn: 0.001-0.300%, Sb: 0.001 to 0.300%, Te: 0.001 to 0.100%, Se: 0.001-0.100%, As: 0.001 to 0.050%, Bi: 0.001 to 0.500%, and Pb: 0.001-0.500% The steel material according to any one of claims 1 to 4, comprising one or more of the following:
6. The steel material according to any one of claims 1 to 5, wherein the Sn content is 0.004% or less.
7. The steel material according to any one of claims 1 to 6, wherein the martensite area ratio at a position of 1 / 2 of the thickness of the steel material is 90% or more.
8. The steel material according to any one of claims 1 to 7, wherein the thickness of the steel material is 2.5 mm or more.
Citation Information
Patent Citations
Annealing method of tool steel, production method of annealed material for tool steel, annealed material for tool steel, tool steel using the same and tool
JP2005226150A
High-strength thick-wall electric resistance welded steel tube having excellent hardenability and decarburization resistance, and its manufacturing method
JP2007056283A
Medium carbon steel sheet and its production method
JP2007291468A
Steel sheet and method of manufacturing the steel sheet
JP2018024907A
Steel sheet and method of manufacturing the steel sheet
JP2018024908A